Theory and applications of heat transfer in humans - Shrivastava, Devashish, 1976- (Wiley, 2018)
An authoritative guide to theory and applications of heat transfer in humans' Theory and Applications of Heat Transfer in Humans 2V Set offers a reference to the field of heating and cooling of tissue, and associated damage. The author'a noted expert in the field'presents, in this book, the fundamental physics and physiology related to the field, along with some of the recent applications, all in one place, in such a way as to enable and enrich both beginner and advanced readers.' The book provides a basic framework that can be used to obtain 'decent' estimates of tissue temperatures for various applications involving tissue heating and/or cooling, and also presents ways to further develop more complex methods, if needed, to obtain more accurate results.' The book is arranged in three sections: The first section, named 'Physics', presents fundamental mathematical frameworks that can be used as is or combined together forming more complex tools to determine tissue temperatures; the second section, named 'Physiology', presents ideas and data that provide the basis for the physiological assumptions needed to develop successful mathematical tools; and finally, the third section, named 'Applications', presents examples of how the marriage of the first two sections are used to solve problems of today and tomorrow. This important text is the vital resource that: -Offers a reference book in the field of heating and cooling of tissue, and associated damage.-Provides a comprehensive theoretical and experimental basis with biomedical applications -Shows how to develop and implement both, simple and complex mathematical models to predict tissue temperatures -Includes simple examples and results so readers can use those results directly or adapt them for their applications Designed for students, engineers, and other professionals, a comprehensive text to the field of heating and cooling of tissue that includes proven theories with applications. The author reveals how to develop simple and complex mathematical models, to predict tissue heating and/or cooling, and associated damage.'